A Gender Studies corpus: why, how and for what? (Revista de Estudos da Linguagem, 2024)
This work presents an important part of a research that aims to contribute to terminological and translational studies as well as corpus studies, upon analyzing the units that represent and transmit specialized knowledge in a field of soaring academic evolution in Brazil and that discusses urgent social demands, Gender Studies. To do so, this article will expose a fundamental stage of any research regarding corpus: the definition of the field to be analyzed and the clipping of texts based on reliable criteria that are able to represent such targeted field of study. Accordingly, the main intent of this article is to convey why, how and for what purpose it was proposed to relate Corpus Linguistics with Gender Studies from the compilation of a corpus, introducing therefore a history of the selected field that justifies the analysis proposed and its characterization as a specialized field. In addition, the theoretical references supporting the work and the analyzed corpus stands out, compiled based on the criteria of Corpus Linguistics and composed by the two main journals in the field of Gender Studies in Brazil, the Revista Estudos Feministas and Cadernos Pagu. In conclusion, it defends the importance of producing linguistic and terminological researches that converse with contemporary and urgent social demands.